(untitled) (Journal of Rangpur Medical College, 2023)
Background: Silver diamine fluoride (SDF) can be used for active carious lesions in primary teeth and can be applied in dental clinics, in school, or in community-based settings with simple armamentarium and minimal support. Silver diamine fluoride causes darkening of carious enamel and dentin after its application. Method: An electronic literature search in Web of Science, Scopus, Science Direct, PubMed, Google Scholar, African Journal Online, Researchgate, and Google was done in June 2023. Search terms and keywords were combined by Boolean operators. Four independent investigators (research assistants) screened titles, abstracts, and full text of publications. The inclusion criteria were original research articles ( human studies) carried out in African regions and including observational studies (cohort, case-control, cross-sectional), experimental studies (clinical trials, randomized or not) designs, case reports, and case series investigating parents, caregivers, guardians or children acceptability or acceptance of silver diamine fluoride treatment procedure and post-treatment blackening/staining of teeth. Systematic reviews and review articles were excluded. Results: One article was included as it was assessed to meet the aim of the review. It was a hospital-based study. Parental acceptance of silver diamine fluoride treatment with its black staining was assessed using the Likert scale. Acceptance of post-treatment staining of teeth among parents was higher in posterior teeth than in anterior teeth. Conclusion: Only one study on the acceptability or acceptance of silver diamine fluoride treatment procedure and post-treatment staining of teeth was identified among African parents. More studies from the diverse ethnic population in Africa will contribute to the existing literature. J Rang Med Col. September 2023; Vol. 8, No. 2: 53-55